Method (Stimulation Endorphin, Oxytosin and Sugestive) to Increase The Production of Breast Milk and Involution of Uters On Post Partum - Sefrina Rukmawati; Puji Astutik; Ambar Dwi Retnoningrum (Universitas STRADA Indonesia, 2020)
This research uses quasi experiment post test only design. The study used consecutive sampling. The independent variable Method (Stimulation Endorphin,Oxytosin and Sugestive), dependent variable Smoothness of breast milk and Uteric Involution. data collection using observation sheets. The study population and sample were 30 respondents with purposive sampling technique. The results of the study of 30 respondents, 15 respondents were not given speos method therapy almost all respondents, namely 13 respondents not producing smooth milk (86.6%) and 10 respondents were abnormal Uterus (66.67%), while 15 respondents were given Method (Stimulation endorphin, oxytocin and suggestive) almost All respondents, 14 respondents, were producing breast milk smoothly (93.3%). T-test results obtained pvalue = 0,000 ≤ α = (0.05), so that Ha is accepted. There is an influence of Method (Stimulation endorphin, oxytocin and suggestive) to increase milk production and involution of the uterus in post partum